Developing Ardgotic Game to Improve Logarithm Learning Outcomes - Prameshela, Rakeltamara Y.; Kristiyanto, Wahyu H.; Mampouw, Helti L. (International Journal of Active Learning, 2021)
This research aims to produce ardgotic learning media that can improve student learning outcomes on logarithm.Ã‚Â This research consists of 5 development steps, namely analysis, design, development, implementation and evaluation. Ardgotic is a game developed from an othello type board game that requires players to win the games where logarithm is the topic. The results of this media validation reached 94.54%. Trials on 32 students of class X SMK showed a practically rate of 85.71%, both of which were in the very good category. The use of ardgotic media can improve learning outcomes logarithm by 0.697 or a moderate increase. Students find the appearance of the media attractives and the media can motivate them to learn logarithms. These results indicate that ardgotic media can be used to learn mathematics in different ways.